2019
DOI: 10.1093/mnras/stz2628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain alignment efficiency on synthetic dust polarization observations of molecular clouds

Abstract: It is well known that the polarized continuum emission from magnetically aligned dust grains is determined to a large extent by local magnetic field structure. However, the observed significant anticorrelation between polarization fraction and column density may be strongly affected, perhaps even dominated by variations in grain alignment efficiency with local conditions, in contrast to standard assumptions of a spatially homogeneous grain alignment efficiency. Here we introduce a generic way to incorporate he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…molecular cloud complex Vela C (Fissel et al 2016). The suggested possible explanations for this trend are due to: (1) the loss of the grain alignment because of the grain growth (Bethell et al 2007;Brauer et al 2016) or scattering and absorption of photons at high density (King et al 2018(King et al , 2019; (2) the optical depth effect (Dowell 1997;Hildebrand et al 1999); or (3) the unresolved complex B-field structures along the line of sight. It is, however, beyond the scope of this paper to constrain them using only these data.…”
Section: Polarization Propertiesmentioning
confidence: 99%
“…molecular cloud complex Vela C (Fissel et al 2016). The suggested possible explanations for this trend are due to: (1) the loss of the grain alignment because of the grain growth (Bethell et al 2007;Brauer et al 2016) or scattering and absorption of photons at high density (King et al 2018(King et al , 2019; (2) the optical depth effect (Dowell 1997;Hildebrand et al 1999); or (3) the unresolved complex B-field structures along the line of sight. It is, however, beyond the scope of this paper to constrain them using only these data.…”
Section: Polarization Propertiesmentioning
confidence: 99%
“…King et al (2018) highlighted the importance of properly treating grain alignment physics in modeling synthetic observations. Corrections for mimicking RAT alignment were later investigated in King et al (2019) without invoking the full complexity of RAT physics.…”
Section: Origin Of Dust Polarizationmentioning
confidence: 99%
“…In more recent work employing MHD simulations, King et al (2018) and Seifried et al (2019) find that the ordered and random components are more complicated than modeled by Jones et al (1992). While Jones et al (2015a) argued that a slope of α = −1 indicated complete loss of grain alignment due solely to loss of radiation that aligns grains by radiative torques (Lazarian & Hoang 2007;Andersson et al 2015), King et al (2019) find that including a dependency on local density for grain alignment efficiency can help explain these trends seen in large molecular clouds.…”
Section: Polarization -Intensity Relationmentioning
confidence: 99%